A difficult-to-diagnose fibromatosis-like metaplastic carcinoma of the breast: a case report - Daiki Takatsuka; Hiroyuki Ogura; Yuko Asano; Akiko Nakamura; Kei Koizumi; Norihiko Shiiya; Satoshi Baba (Surgical Case Reports, 2021)
Abstract Background Fibromatosis-like metaplastic carcinoma (FLMCa), classified as a metaplastic carcinoma of the breast, is a very rare type of metaplastic carcinoma. We report a case of FLMCa that was difficult to diagnose. Case presentation The patient was a 56-year-old postmenopausal woman who presented with a left-sided breast mass. A 1.3-cm irregular mass was found in the lower outer quadrant of the left breast on breast ultrasonography. She underwent core needle biopsy and vacuum-assisted biopsy, but the pathological findings only revealed inflammatory cell infiltration and a high level of fibrosis, with no malignant findings. At 3 months follow-up, she underwent a repeat breast ultrasonography, which revealed an increase in the size of the mass to 1.8 cm, and a repeat core needle biopsy, which showed a few spindle cells and squamous cells positive for cytokeratin (CK)5/6 and AE1/AE3, leading to the suspicion of FLMCa. Since the amount of tissue was insufficient to establish a definitive diagnosis, she underwent a lumpectomy. We found low-grade and slightly atypical spindle cells and partly atypical spindle cell carcinoma and squamous cell carcinoma. CK5/6 and α-SMA were positive, thus confirming FLMCa. Because the margins on the edge of the nipple side and anterior side were “ink on tumor”, she underwent a mastectomy and sentinel lymph node biopsy. After the surgery, she received adjuvant chemotherapy. At 3 years and 8 months of follow-up, no recurrent or metastatic lesions were identified in her body. Conclusions FLMCa should be considered in the differential diagnosis when collagenous fibers are proliferating and malignancy is clinically suspected. Immunohistochemical analysis may be helpful in confirming this diagnosis.